Acanthosis nigricans vulgaris. A marker of hyperinsulinemia. - Garofalo, L.; Biscozzi, A.M.; Mastrandrea, V.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
Acanthosis nigricans (AN) is a syndrome with variable clinical significance ranging from marker of moderate endocrine imbalance to marker of malignancy. The most frequent form of AN, which therefore could be called AN vulgaris, is AN associated to obesity. Here is reported a case of AN associated to obesity. Physicians should be aware that this form is due to insulin resistance secondary to obesity and that insulin resistance, when the pancreas works, is responsible for hyperinsulinemia. The latter is responsible in malesfor AN and in females for AN and hyperandrogenemia (HA). The treatment of AN vulgaris is based, besides the topical therapy, on the correction of obesity. When the latter goal cannot be achieved, metformin hydrochloride should be given. This biguanide drug increases both the peripheral response to insulin and the cellular glucose metabolism. Moreover, it decreases the delayed glucose intestinal absorption and inhibits hepatic glucogenesis.